Truncation of the C-Terminal Acidic Transcriptional Activation Domain of Herpes Simplex Virus VP16 Renders Expression of the Immediate-Early Genes Almost Entirely Dependent on ICP0 - Mossman, Karen L. (American Society for Microbiology, 1999)
The herpes simplex virus (HSV) proteins VP16 and ICP0 play key roles in stimulating the onset of the viral lytic cycle. We sought to explore the regulatory links between these proteins by studying the phenotypes of viral mutants in which the activation functions of both were simultaneously inactivated. This analysis unexpectedly revealed that truncation of the C-terminal transcriptional activation domain of VP16 (allele V422) in an ICP0-deficient background almost completely eliminated immediate-early gene expression and virus replication in Vero and HEL cells. The doubly mutant viral genome persisted in a quiescent state for at least 10 days in HEL cells infected at high multiplicity and could be reactivated by superinfection with wild-type HSV. In contrast, the in1814 VP16 mutation produced a markedly less severe phenotype in the same ICP0-deficient background. These data demonstrate that expression of the immediate-early genes requires ICP0 when the C-terminal activation domain of VP16 is deleted and raise the possibility that the in1814 form of VP16 retains a residual ability to stimulate gene expression during virus infection.